Architecture control and model identification of a omni-directional mobile robot - A. Paulo Moreira (2005)
This paper presents a architecture control and model identification of a onmi-Directional Mobile Robot It is divided into the three stages. Stage one proposes a procedure for dynamic model identification and control of the "motor + reduction + encoder" process of the Robot's Motors. Second, proposes the identification of a dynamic model for the whole mobile robot considering it as a multi-variable system. Third, presents a algorithm for perfect trajectory tracking of Omni-Directional Mobile Robots, based on restriction on motor's velocities. This algorithm combines the restriction on motor's velocities and the kinematic model of mobile robot to generate ideal drive velocities for the mobile robot to follow the trajectories correctly with the best possible performance.